2015
DOI: 10.1021/nl505011f
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interfacial Oxide in High-Efficiency Graphene–Silicon Schottky Barrier Solar Cells

Abstract: The advent of chemical vapor deposition (CVD) grown graphene has allowed researchers to investigate large area graphene/n-silicon Schottky barrier solar cells. Using chemically doped graphene, efficiencies of nearly 10% can be achieved for devices without antireflective coatings. However, many devices reported in past literature often exhibit a distinctive s-shaped kink in the measured I/V curves under illumination resulting in poor fill factor. This behavior is especially prevalent for devices with pristine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
276
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(286 citation statements)
references
References 33 publications
9
276
1
Order By: Relevance
“…The reduced photocurrent responsivity R c ( fig.5b) and increased photovoltage responsivity R v ( fig.5c) for low light intensities can be qualitatively explained due to the presence of the interfacial oxide layer in the GIS device according to the suggestion in [47]. Photogenerated holes build-up at the interface due to the presence of the interfacial oxide layer [47].…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The reduced photocurrent responsivity R c ( fig.5b) and increased photovoltage responsivity R v ( fig.5c) for low light intensities can be qualitatively explained due to the presence of the interfacial oxide layer in the GIS device according to the suggestion in [47]. Photogenerated holes build-up at the interface due to the presence of the interfacial oxide layer [47].…”
mentioning
confidence: 89%
“…Photogenerated holes build-up at the interface due to the presence of the interfacial oxide layer [47]. The oxide layer poses a tunneling barrier for charge carriers and an electric field facilitates the tunneling of charge carriers through this barrier.…”
mentioning
confidence: 99%
“…[4,5] These heterostructures can act as rectifiers, potential barrier modulators, photodetectors, photovoltaic devices, chemical sensors, etc. [6][7][8][9][10][11][12] Even though GS Schottky diodes are relatively simple to fabricate, their performance is limited by the various factors which can be measured by the ideality factor (η). Previous studies report unusually wide-range ideality factors of the GS devices, η = 1.1-33.5.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies report unusually wide-range ideality factors of the GS devices, η = 1.1-33.5. [6][7][8][9][10][11][12] To design and implement efficient practical GS www.advelectronicmat.de the above-mentioned effects. From the analysis of experimental data and Raman spectroscopic study, we extracted and confirmed various physical parameters such as the voltagedependent carrier concentration of graphene, interface state density, and ideality factors.…”
Section: Introductionmentioning
confidence: 99%
“…A rapid thermal annealing process was applied to clean the Si surface and form a thin oxide layer. The thin oxide layer is effective for reducing the reverse saturation current and thus improves the device property [19]. Silicon was used with a thin oxide layer, which is the same for all the devices [20].…”
Section: Methodsmentioning
confidence: 99%